Reversed-phase chromatographic separation and downstream precipitation of lupane- and oleanane-type triterpenoids: experiments and modeling based on the method of moments - Azenha, Ivo S. (2021)
The reversed-phase chromatographic separation of two triterpenic acids (TTAs), betulinic and oleanolic acids, using a triacontyl (C30) stationary phase was addressed in this work. Methanol, water, acetonitrile, ethanol, isopropanol, ethyl acetate, acetone and mixtures thereof were tested, and the best mobile phase to conduct the separation was found to be methanol/acetonitrile 50/50 (%, v/v) at 23 °C, taking into account parameters like selectivity, resolution and TTAs solubility. The method of moments was used to determine the equilibrium constants of isotherms, the axial dispersion coefficients and the global linear driving force coefficients of pure betulinic and pure oleanolic acids. These parameters were then successfully validated by modeling unary and binary breakthrough curves. Simulated moving bed calculations showed that betulinic and oleanolic acids can be both obtained with purity of 99.2 % and productivity of 56.2 kg/(m3adsorbent day) using the packing material of an Acclaim C30 column with a 1-1-1-1 configuration with columns of 7.5 cm long. Finally, in order to recover the two TTAs from the SMB extract and raffinate streams, water was envisioned as a precipitation agent. Accordingly, the solubility of each TTA was measured in methanol/acetonitrile 70/30, 50/50, and 30/70 (%, v/v) modified with water. The obtained results showed that adding 65 % (%, v/v) of water it is possible to precipitate 98 % of the dissolved TTAs in all the tested methanol/acetonitrile mixtures.